Catalytic Properties of High Nitrogen Content Carbonaceous Materials. (2nd December 2022) - Lepre, Enrico; Rat, Sylvain; Cavedon, Cristian; Seeberger, Peter H.; Pieber, Bartholomäus; Antonietti, Markus; López‐Salas, Nieves
Abstract: The influence of structural modifications on the catalytic activity of carbon materials is poorly understood. A collection of carbonaceous materials with different pore networks and high nitrogen content was characterized and used to catalyze four reactions to deduce structure–activity relationships. The CO2 cycloaddition and Knoevenagel reaction depend on Lewis basic sites (electron‐rich nitrogen species). The absence of large conjugated carbon domains resulting from the introduction of large amounts of nitrogen in the carbon network is responsible for poor redox activity, as observed through the catalytic reduction of nitrobenzene with hydrazine and the catalytic oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine using hydroperoxide. The material with the highest activity towards Lewis acid catalysis (in the hydrolysis of (dimethoxymethyl)benzene to benzaldehyde) is the most effective for small molecule activation and presents the highest concentration of electron‐poor nitrogen species. Abstract : Carbon materials are attractive alternatives to metal catalysts in terms of price and reduced environmental impact. However, the influence of structural modifications on the catalytic activity of carbon materials is poorly understood. General trends in the catalytic activity of nitrogen‐doped carbons are identified using a holistic approach to carbocatalysis.